Closed-loop cascade nanozyme strategy for mutually reinforced catalytic and mild-temperature photothermal therapeutic effects - Fan Yang; Chunyu Yan; Nannan Li; Xinxiu Jiang; Baojie Du; Peirong Bai; Liping Li; Ruiping Zhang (Journal of Nanobiotechnology)
Abstract Nanocatalysis coupled with photothermal therapy is a potent anti-cancer approach, yet its clinical utility is limited by low concentration of tumor substrate, redox interference, and risks of overheating normal tissues. Herein, we propose an innovative closed-loop nanozyme approach that leverages the synergistic effects of catalytic and mild photothermal therapy (mPTT) to address aforementioned challenges. The strategy features a folic acid-functionalized iron single-atom catalyst (FeNC-FA), designed to exhibit exceptional multienzymatic capabilities and an optimal photothermal response. In the system, the engineered FeNC-FA is capable of inducing reactive oxygen species (ROS) storm and depleting glutathione (GSH) in the specific tumor microenvironment (TME) to initiate ferroptosis. Concurrently, the accumulation of ROS effectively cleaves heat shock proteins (HSPs), thereby enhancing mPTT. An intriguing aspect is that the increased temperature within the TME further facilitates the conversion of H2O2 to O2, alleviating hypoxia and providing a positive feedback circuit to boost catalytic therapy. Additionally, the advanced photoacoustic (PA) imaging capabilities of FeNC-FA allow for self-monitoring of their accumulation at tumor sites, thereby guiding the mPTT process. Taken together, it provides a PA image-guided, mutually reinforced catalytic and mild photothermal synergistic tumor therapy both in vitro and in vivo. This targeted and synergistic strategy holds great promise for personalized medicine applications.